Streamlined Data Resource for Digital Forensic and Radiographic Research - Zain, Nur Khofifah; Rosnawati, Emy; Pristiwanto (Proceedings of The ICECRS, 2023)
This dataset, culled from Lens.org, streamlines research on "Digital Forensic" and "Radiographic." It began with 1,112 results, filtered down to 924 journal articles, further refined to 15 documents within 2002-2012 in the realm of "Law." Notable institutions include Katholieke Universiteit Leuven and Goethe University Frankfurt, with two documents each. The most prolific year was 2010, with ten documents in "Medicine." Active institutions encompassed various subjects. Key authors were Frank Ramsthaler and Guy Willems, each contributing two documents. The document "Possibilities in cooperation with the Virtopsy project" (2007) stood out with 127 open-access articles. Elsevier Ireland Ltd led in publishing, especially in forensic science. This resource aids future research on "Digital Forensic" and "Radiographic," offering valuable insights and facilitating global scientific advancements in these domains. Highlights : Comprehensive Dataset: This dataset offers a comprehensive collection of research materials for digital forensic and radiographic studies, saving time and effort for researchers. Specialized Filters: The use of specialized filters, including document type, date range, and subject matter, ensures precision in search results. Facilitating Insights: This resource empowers researchers to gain valuable insights, explore new avenues, and advance knowledge in the field. Keywords: Digital Forensic, Radiographic, Research Data, Data Collection, Information Retrieval